Primary care treatment of insomnia: study protocol for a pragmatic, multicentre, randomised controlled trial comparing nurse-delivered sleep restriction therapy to sleep hygiene (the HABIT trial). Issue 3 (4th March 2020) - Kyle, Simon D; Madigan, Claire; Begum, Nargis; Abel, Lucy; Armstrong, Stephanie; Aveyard, Paul; Bower, Peter; Ogburn, Emma; Siriwardena, Aloysius; Yu, Ly-Mee; Espie, Colin A
Abstract : Introduction: Insomnia is a prevalent sleep disorder that negatively affects quality of life. Multicomponent cognitive-behavioural therapy (CBT) is the recommended treatment but access remains limited, particularly in primary care. Sleep restriction therapy (SRT) is one of the principal active components of CBT and could be delivered by generalist staff in primary care. The aim of this randomised controlled trial is to establish whether nurse-delivered SRT for insomnia disorder is clinically and cost-effective compared with sleep hygiene advice. Methods and analysis: In the HABIT (Health-professional Administered Brief Insomnia Therapy) trial, 588 participants meeting criteria for insomnia disorder will be recruited from primary care in England and randomised (1:1) to either nurse-delivered SRT (plus sleep hygiene booklet) or sleep hygiene booklet on its own. SRT will be delivered over 4 weekly sessions; total therapy time is approximately 1 hour. Outcomes will be collected at baseline, 3, 6 and 12 months post-randomisation. The primary outcome is self-reported insomnia severity using the Insomnia Severity Index at 6 months. Secondary outcomes include health-related and sleep-related quality of life, depressive symptoms, use of prescribed sleep medication, diary and actigraphy-recorded sleep parameters, and work productivity. Analyses will be intention-to-treat. Moderation and mediation analyses will be conducted and a cost-utility analysis and process evaluation will be performed. Ethics and dissemination: Ethical approval was granted by the Yorkshire and the Humber - Bradford Leeds Research Ethics Committee (reference: 18/YH/0153). We will publish our primary findings in high-impact, peer-reviewed journals. There will be further outputs in relation to process evaluation and secondary analyses focussed on moderation and mediation. Trial results could make the case for the introduction of nurse-delivered sleep therapy in primary care, increasing access to evidence-based treatment for people with insomnia disorder. Trial registration number: ISRCTN42499563